Cyclone Shaheen: the exceptional tropical cyclone of October 2021 in the Gulf of Oman. (1st April 2022) - Terry, James; Al Ruheili, Amna; Boldi, Robert; Gienko, Gennady; Stahl, Henrik
Abstract : Early October 2021 saw Cyclone Shaheen track westward across the far northern Arabian Sea, penetrate the Gulf of Oman and strike the northeast Oman coastline – the first storm to make such a unique landfall in more than 130 years. This paper describes how the unusual cyclogenesis location, favourable initial trajectory and steering, conducive environmental conditions and anomalously warm sea‐surface temperatures were the main influences responsible for Shaheen 's extraordinary genesis, intensification and remarkable geographical landfall.